Action Today to Stop Polution: Sosialisasi Pengelolaan Sampah Plastik Menjadi Ecobrick di Desa Kalimacan Kabupaten Sragen - Widianto Atmojo, Idam Ragil; Matsuri, Matsuri; Chumdari, Chumdari; Adi, Fadhil Purnama; Ardiansyah, Roy; Saputri, Dwi Yuniasih (DEDIKASI: Community Service Reports, 2023)
Indonesia is the second largest country that produces plastic waste in the world. Plastic waste is decomposed in about 1000 years. Plastic waste has a negative impact on the environment, such as the accumulation of garbage, which causes environmental pollution. Correct steps are needed to overcome these problems. One of the right strategies to overcome this problem is by using the 5R method, namely Reduce, Reuse, Recycle, Replace, and Replant which we should apply in dealing with plastic waste. However, not all areas have waste disposal facilities. Especially nowadays a landfill is a necessity, for that we need a landfill. The solution to this problem is the manufacture of ecobrick products, in which these products can be made easily with makeshift tools and materials. The purpose of this socialization is to increase public awareness, especially in the Malangan Hamlet area, RT 04, Kalimacan, Kalijambe, Sragen Regency regarding ecobrick products as a step to care for the environment. The method used is counseling in the form of lectures and demonstrations. The results obtained are that people can understand the importance of maintaining cleanliness and environmental health by sorting waste properly, and are able to provide ecobrick products in the form of shoe containers, both as personal and community needs. Ecobrick has a positive impact on society by reducing plastic waste and turning it into a livelihood opportunity.